Effectiveness of one-dose versus two-dose varicella vaccine in children in Qingdao, China: a matched case-control study - Ping Hu; Feng Yang; Xiaofan Li; Yang Wang; Tingting Xiao; Han Li; Wencheng Wang; Jing Guan; Shanpeng Li (Taylor & Francis Group, 2021)
To evaluate whether two-dose of varicella vaccine would provide a better protection to children from varicella than one-dose, we conducted a 1:3 matched case-control study in children in Qingdao, China. A total of 509 varicella cases aged 6-11 y were collected from the China Information System for Disease Control and Prevention (CISDCP). And 1,527 controls, who did not suffer from varicella, were selected and matched with cases by age and class. The varicella vaccine effectiveness (VE) and corresponding 95% confidence interval (95% CI) were calculated. The vaccination coverage rate of one-dose varicella vaccine in the cases was 52.9%, while for the controls was 59.1%. And the two-dose vaccination rate in the cases and controls were 4.3% and 14.5%, respectively. A statistically significant difference was found in the immunization history between the cases and controls (P < .001). The overall varicella VE was 56.1% (95% CI: 45.0%-64.9%), and the VE of two-dose vaccination (81.6%, 95% CI: 70.5%-88.4%) was substantially higher than that of one-dose vaccination (44.7%, 95% CI: 31.6%-55.4%). For less than 2 y, 2-4 y, 4-6 y, and more than 6 y after only one-dose vaccination, the varicella VE were 96.6% (95% CI: 75.0%-99.5%), 81.2% (95% CI: 55.6%-92.0%), 60.8% (95% CI: 46.8%-70.2%), and 18.0% (95% CI: 4.3%-35.6%), respectively. The varicella VE gradually decreased over time (P for trend < 0.001). It is recommended that the coverage of varicella vaccine should be increased and two-dose of varicella vaccine should be included in the National Immunization Program of China.